Polylactic acid electrospun membrane loaded with cerium nitrogen co-doped titanium dioxide for visible light-triggered antibacterial photocatalytic therapy - Lv, Hanlin; Xia, Xiaomin; Sun, Sa; Niu, Zhaojun; Liu, Jie; Li, Xue (Frontiers in Microbiology, 2024)
Wound infection caused by multidrug-resistant bacteria poses a serious threat to antibiotic therapy. Therefore, it is of vital importance to find new methods and modes for antibacterial therapy. The cerium nitrogen co-doped titanium dioxide nanoparticles (N-TiO2, 0.05Ce-N-TiO2, 0.1Ce-N-TiO2, 0.2Ce-N-TiO2) were synthesized using hydrothermal method in this work. Subsequently, electrospinning was employed to fabricate Polylactic acid (PLA) electrospun membranes loaded with the above-2 mentioned nanoparticles (PLA-N, PLA-0.05, PLA-0.1, PLA-0.2). The results indicated that cerium and nitrogen co-doping have enhanced the visible light photocatalytic efficiency of TiO2 nanoparticles and enabled the conversion of ultraviolet light into harmless visible light. The photocatalytic reaction under visible light irradiation induced the generation of ROS, which could effectively inhibit the bacterial growth.The antibacterial assay showed that it was effective in eliminating S. aureus and E. coli and the survival rates of two types of bacteria under 30 minutes of irradiation were significantly below 20% in the PLA-0.2 experimental group. Moreover, the bactericidal membranes also have excellent biocompatibility performance. This Biofriendly and biodegradable membrane may be applied to skin trauma and infection in the future to curb drug-resistant bacteria and provide more alternative options for antimicrobial therapy.